2011
DOI: 10.1371/journal.pone.0027241
|View full text |Cite
|
Sign up to set email alerts
|

Music and Emotions in the Brain: Familiarity Matters

Abstract: The importance of music in our daily life has given rise to an increased number of studies addressing the brain regions involved in its appreciation. Some of these studies controlled only for the familiarity of the stimuli, while others relied on pleasantness ratings, and others still on musical preferences. With a listening test and a functional magnetic resonance imaging (fMRI) experiment, we wished to clarify the role of familiarity in the brain correlates of music appreciation by controlling, in the same s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
313
4
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 367 publications
(350 citation statements)
references
References 61 publications
21
313
4
12
Order By: Relevance
“…The questionnaire While literature does suggest increased emotional response to familiar songs Pereira et al, 2011), original songs were chosen as they would not interact with pre-learned expectations of the lyrics, or introduce variability in episodic memories linked to familiar songs. In addition, the music was written and recorded for the same instrument, by the same composer, and sung by the same voice, which minimises variability across stimuli.…”
Section: Stimulimentioning
confidence: 99%
“…The questionnaire While literature does suggest increased emotional response to familiar songs Pereira et al, 2011), original songs were chosen as they would not interact with pre-learned expectations of the lyrics, or introduce variability in episodic memories linked to familiar songs. In addition, the music was written and recorded for the same instrument, by the same composer, and sung by the same voice, which minimises variability across stimuli.…”
Section: Stimulimentioning
confidence: 99%
“…The main structures associated with music emotion perception include the bilateral auditory cortices, orbitofrontal cortex, cingulate cortex, parahippocampal gyrus, right nucleus accumbens, and the bilateral amygdala (Kolesch, 2014). A few functional magnetic resonance imaging (fMRI) studies (Menon & Levitin, 2005;Pereira et al, 2011) found evidence of activity in emotion-related brain structures even if subjects were not concentrating on an emotion-related task during scanning. However, those studies did not include an explicit emotion-listening condition.…”
Section: Introductionmentioning
confidence: 99%
“…This allowed subjects to move away from possible mental states arising from such target detection tasks that may not be characteristic of brain's behaviour in more natural, attentive situations. Such paradigm constitutes an unusual approach as opposed to the usual practice in research studies focusing on auditory processing in the brain (Koelsch et al, 2009, Pallesen, Brattico, Bailey, Korvenoja, Koivisto, Gjedde, & Carlson, 2010Pereira, Teixeira, Figueiredo, Xavier, Castro, & Brattico, 2011;Brattico, Alluri, Bogert, Jacobsen, Vartiainen, Nieminen, & Tervaniemi, 2011;Levitin & Menon, 2003;Janata, Tillmann, & Bharucha, 2002). Even if still ecologically significant, findings derived from traditional approaches employing artificially controlled musical stimuli would need to be validated against results coming from rich, naturalistic approaches, more representative of the complex auditory phenomena the brain has evolved to respond to.…”
Section: Introductionmentioning
confidence: 99%